Observational study on patterns of neuromuscular blockade reversal. Issue 1 (December 2016) - Dubovoy, Timur; Housey, Michelle; Devine, Scott; Kheterpal, Sachin
Abstract Background Using electronic health record data, we hypothesized that larger reversal doses are used for patients with deeper levels of neuromuscular blockade (NMB) as evidenced by the last recorded TOF measurement. We also examined if dosing regimens reflect current practice guidelines of using ideal body weight (IBW) for NMB agents and total body weight (TBW) for neostigmine. Methods This is a retrospective observational study of adult, ASA 1–4 patients who underwent general anaesthesia and received non-depolarizing NMB agents between 01/01/2004 and 12/31/2013. For the primary outcome, percentages of cases receiving neostigmine and median doses administered for each subjective train-of-four (TOF) category were calculated. Secondary analyses evaluated associations between NMB dosing and neostigmine administration based on Body Mass Index (BMI) categories. Results A total of 135, 633 cases met inclusion criteria for the study. There was no clinically significant difference in median neostigmine dosing based on last TOF count prior to reversal administration: 37.5 mcg/kg for TOF of 4/4 vs. 37.9 mcg/kg for TOF of 0/4 for the total neostigmine dose. Significantly higher number of patients with lower TOF counts received additional neostigmine administration: 5.7 % for 0/4 vs. 1.5 % for 4/4 TOF counts. The median times to extubation following neostigmine administration were clinically similar across TOF count categories. The median doses for neostigmine based on TBW decreased with higher BMI categories and were significantly different between the lowest and highest categories: 42.8 mcg/kg vs 30.8 mcg/kg for total doses (p < .0001) respectively. The percentages of cases requiring reversal in addition to the initial dose increased with increasing BMI categories and were 2.1 % for BMI < 18 vs. 3.3 % for BMI ≥ 40. The total median dose of NMB agents in ED95 equivalents per IBW increased from 2.9 in the Underweight category to 4.2 in the Class III Obese category. The majority of patients in the pancuronium subgroup received very low ED95 equivalent dose of 0.1 and did not require reversal. Patients receiving cisatracurium were given significantly higher median ED95 equivalent dose of 5.6 vs 2.8–3.9 compared to other intermediate acting NMB agents, while receiving clinically similar doses of neostigmine. Conclusions Neither neostigmine dosing nor times to extubation were affected by the depth of the neuromuscular blockade prior to reversal. The need for additional reversal, or rescue, correlated strongly with the depth of NMB. There was significant variability in neostigmine dosing across the BMI categories. Underweight patients received relatively lower NMB doses while simultaneously receiving relatively higher reversal doses, and the opposite was true for patients with BMI >40.